Influence of salt and herbal substance on the drying and reconstitution performance of Bombay duck, Harpodon nehereus - Vikash Chandra Roy; Md. Kamal; Md. Faridullah; Syed Ariful Haque; Md. Shaheed Reza (Journal of Fisheries, 2014)
Effects of salt, chili and turmeric powder on the production of high quality dried fish products from Bombay duck (Harpodon nehereus) under open sun drying was investigated. Five different types of dried products (T1-T5) were produced and studied. Moisture content in T3 decreased more rapidly to below 16% within 28 hrs of drying compared to those treated with other treatments (temperature varies from 24.6°C to 34°C and relative humidity varies between  60% and 48%) . Drying process was very slow in control samples where it took 32 hrs for reaching the moisture level to 18.75%. Both turmeric and chili powders had strong repellency effect against insect infestation. Bombay duck treated with salt and herbal products were less infested by the blowfly whereas samples dried under control treatment were severely infested by blowfly.